Uptake and engagement with digital mental health in the workplace: A mixed-methods analysis of the EMPOWER trial - Peeters, Stijn B.; de Mul, Marleen; Thielen, Frederick W.; Sinokki, Marjo; Staszewska, Kaja; Salvador-Carulla, Luis; Lukersmith, Sue; Olaya, Beatriz; Hakkaart-van Roijen, Leona (Elsevier BV, 2026)
This study examined contextual factors influencing the uptake and use of the EMPOWER digital mental health platform, implemented in small and medium-sized enterprises and public agencies in Spain, Poland, Finland, and the United Kingdom. The platform was developed within an EU-funded project to promote workplace mental health and evaluated in a randomised controlled trial assessing its effectiveness and cost-effectiveness. A mixed-methods design was applied combining logistic regression analyses of baseline employee data with qualitative semi-structured interviews exploring barriers and facilitators to engagement. Results indicated that successful uptake was supported by strong employer involvement, a positive workplace culture, clear communication of benefits and data privacy, tailoring of content to employee needs, and available technical support. Barriers included insufficient communication, limited organisational support, lack of allocated time for use, unclear instructions, and concerns about anonymity. Employers often expressed reluctance to take responsibility for facilitating implementation, reflecting low organisational readiness. While the platform itself was generally regarded as user-friendly, its integration into daily workplace practices was inconsistent, with many employees using it outside of working hours. In conclusion, effective and sustainable implementation of digital workplace mental health interventions requires more active stakeholder engagement, clearer and sustained communication strategies, and alignment with organisational policies and structures. Addressing these contextual factors is essential for maximising uptake and ensuring that digital health platforms such as EMPOWER achiever their intended impact in supporting mental health at work.